2008
DOI: 10.1115/1.2931508
|View full text |Cite
|
Sign up to set email alerts
|

The Inverse Vortex Wake Model: A Measurement Analysis Tool

Abstract: To reduce the level of uncertainty associated with current rotor aerodynamics codes, improved understanding of rotor aerodynamics is required. Wind tunnel measurements on model rotors contribute to advancing our knowledge on rotor aerodynamics. The combined recording of blade loads and rotor wake is desired, because of the coupled blade and wake aerodynamics. In general, however, the small size of model rotors prohibits detailed blade load measurements; only the rotor wake is recorded. To estimate the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Wind Energ. Sci., 1, 89-100, 2016 www.wind-energ-sci.net/1/89/2016/ The fact that γ chordwise is distributed over such a large area of the root might explain that the root vortex does not present a well-defined, distinctive structure, as Vermeer et al (2003), Massouh and Dobrev (2007), and Haans et al (2008) reported in their experimental wake studies of different wind turbines. Furthermore, the existence of two adjacent root regions with counter-rotating γ chordwise might also explain the fast diffusion of the root vortex reported by Ebert and Wood (2001) and Sherry et al (2013).…”
Section: The Origin Of the Root Vortexmentioning
confidence: 98%
See 1 more Smart Citation
“…Wind Energ. Sci., 1, 89-100, 2016 www.wind-energ-sci.net/1/89/2016/ The fact that γ chordwise is distributed over such a large area of the root might explain that the root vortex does not present a well-defined, distinctive structure, as Vermeer et al (2003), Massouh and Dobrev (2007), and Haans et al (2008) reported in their experimental wake studies of different wind turbines. Furthermore, the existence of two adjacent root regions with counter-rotating γ chordwise might also explain the fast diffusion of the root vortex reported by Ebert and Wood (2001) and Sherry et al (2013).…”
Section: The Origin Of the Root Vortexmentioning
confidence: 98%
“…Many wind tunnel experiments with model wind turbines confirmed this. For instance, Massouh and Dobrev (2007) and Haans et al (2008) also came to that conclusion after studying a wind turbine rotor wake with particle image velocimetry (PIV) and hot film wake measurements, respectively. Furthermore, Ebert and Wood (2001) and Sherry et al (2013) observed by means of PIV (among other measurement techniques) that the root vortex diffuses very rapidly.…”
Section: The Root Vortexmentioning
confidence: 99%
“…The inverse vortex wake model of Haans et al [16] is numerically discretized in order to increase its flexibility and computational efficiency. Furthermore, its capabilities are extended to yawed flow conditions.…”
Section: Determining the Angle Of Attack And Blade Loadsmentioning
confidence: 99%
“…The current paper presents an updated version of the inverse vortex wake method discussed in [16]. Furthermore, blade loads and inflow conditions at the rotor plane are discussed that result from application of the analysis tool to near-wake measurements on a model rotor subject to yawed flow conditions.…”
Section: Determining the Angle Of Attack And Blade Loadsmentioning
confidence: 99%
See 1 more Smart Citation